Perbedaan Nilai Rerata Vep1 % Prediksi Dan Vep1/ Kvp% Antara Orang Dengan Indeks Massa Tubuh Normal Dan Di Atas Normal Di Universitas Muhammadiyah Surakarta - Putra, Dhanista Hastinata Sukarna, dr. Riana Sari Sp.P, dr. Sri Wahyu Basuki, M.Kes (2015)
Background: The impact of obesity can decrease the pulmonary function which the indicator are of value FEV1 % predicted and FEV1/ FVC % on spirometri examination. This value is used to know the existing of obstruction on the breathing way. The obesity absolutley related with the hormonal disorders, so that influences the bronchus smooth muscle's of to be hyperresponsif (bronchocontricti). Aim : To analyze know the differences of mean's value FEV1 % predicted and FEV1/ FVC % between with BMI normal and above normal people in Muhammadiyah Surakarta University. Methode: This research is analityc observational with cross sectional approachment sampling methode used purposive sampling. The sample as much as 70 mens each consist of 35 with BMI normal and 35 BMI above normal people are selected subjects from restriction criteria. The instrument that used is spirometer. Data analyze technique use the non parametic statistic testing because the distribution data is abnormal, as the comparation between two mean's with Mann Whitney use SPSS 20.0 for windows. Result: Based on the data analyze can be conclude that there is significant differences mean's value FEV1 % predicted and FEV1/ FVC % between with BMI normal and above normal people. The value p is 0,002 on the FEV1% group predicted and 0,000 on the FEV1/ FVC % group. Conclusion: That there is difference mean's value the FEV1 % predicted and FEV1/ FVC % between the BMI normal and above normal people in Muhammadiyah Surakarta University.